PENGAWETAN EMPAT JENIS KAYU UNTUK TIANG LISTRIK DENGAN METODA SEL PENUH - Emmy Yetty; Barly Barly (Jurnal Penelitian Hasil Hutan, 1990)
A full cell treatment of four wood species with 5 and 7 percent copper-chrome-arcenic solution  was conducted using small samples  of 18-25 cm in diametre and 30 cm long. The cross cut-ends of the samples were coated to prevent penetration of the preservative  through  these parts. The preservation  process were held for 2 and 4 hours at a pressure  of 8 and 10 atmosphere.                                                                 The result of the test revealed that four wood species (keluntum, medang, manggung   and  puspa) are recommended for  power poles servation. The treatment shchedule  proposed  for four wood  species  is presented in this paper.